TRANSAKSI DIGITAL BANKING DALAM PERSPEKTIF HUKUM ISLAM - Abu Alim (Constitutum: Jurnal Ilmiah Hukum, 2025)
In today's technological era, digital banking transactions have become closely linked to human life, particularly in buying and selling and making payments. Almost everyone has embraced digitalization. This has become a necessity for living in the digital age. Digital banking transactions have become an effective alternative for individuals, groups, institutions, companies, and others due to their cost-effectiveness, convenience, and speed. Digital banking transactions refer to the medium for transactions being a bank. Almost everyone has a bank account, as employees in companies, institutions, and other institutions generally receive benefits, salaries, and other benefits through bank transfers. Consequently, digital banking transactions have become a common practice. So, how does this relate to Islamic law? Is it prohibited? Therefore, this study examines the legal implications of digital banking transactions from an Islamic legal perspective. This study uses a normative juridical research method. The results of the study are that digital banking transactions which have now become a community commodity as a payment medium in buying and selling are a form of permissible activity that does not violate or is subject to haram law as a form of prohibited activity, but this activity is a process of things that include Al-Muamalah al-Adabiyah which means ijab kabul, mutual consent, no coercion from either party, rights and obligations, honesty of traders, no fraud, no forgery, and everything that comes from human senses that is related to the circulation of assets/money.